How and to What Extent Immunological Responses to SARS-CoV-2 Shape Pulmonary Function in COVID-19 Patients - Laveneziana, Pierantonio; Straus, Christian; Meiners, Silke (Frontiers in Physiology, 2021)
COVID-19 is a disease caused by a new coronavirus SARS-CoV-2, primarily impacting the respiratory system. COVID-19 can result in mild illness or serious disease leading to critical illness and requires admission to ICU due to respiratory failure. There is intense discussion around potential factors predisposing to and protecting from COVID-19. The immune response and the abnormal respiratory function with a focus on respiratory function testing in COVID-19 patients will be at the center of this Perspective article of the Frontiers in Physiology Series on “The Tribute of Physiology for the Understanding of COVID-19 Disease”. We will discuss current advances and provide future directions and present also our perspective in this field.